1981
DOI: 10.1099/0022-1317-54-1-103
|View full text |Cite
|
Sign up to set email alerts
|

Differential Distribution of Virus and Histological Damage in the Lower Respiratory Tract of Ferrets Infected with Influenza Viruses of Differing Virulence

Abstract: SUMMARYThe distribution of four strains of influenza virus [A/PR/8/34 (HON 1) and clone 64d (attenuated for ferrets) and clones 64c and 7a (virulent for ferrets) of the recombinant virus A/PR/8/34-A/England/939/69 (H3N2)] in the lower respiratory tract (trachea, bronchi and the hilar, intermediate and outer alveolar zones of the lung) of ferrets was monitored daily for 4 days after intranasal inoculation. On day 1, some animals had high virus titres in all the tissues but in other animals virus was undetectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 21 publications
(23 reference statements)
0
27
0
Order By: Relevance
“…This suggested that influenza virus replicated mainly in areas where bronchial and bronchiolar epithelium predominated. Quantitative estimation of histological damage in the various areas supported this view; lung damage was minimal, but it was localized in the airways and not in the alveoli (Sweet et al, 1981).…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…This suggested that influenza virus replicated mainly in areas where bronchial and bronchiolar epithelium predominated. Quantitative estimation of histological damage in the various areas supported this view; lung damage was minimal, but it was localized in the airways and not in the alveoli (Sweet et al, 1981).…”
Section: Introductionmentioning
confidence: 61%
“…Respiratory infection in ferrets inoculated with human strains of influenza virus mimics that in man, predominating in the upper respiratory tract with some involvement of the lower tract especially for virulent strains (Matsuyama et al, 1980;Sweet et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations